Revitalizing Local Cultural Values through Contextual Islamic Education in the Digital Era - Erwatul Efendi; Baderiah Baderiah (Har Press Indonesia, 2025)
This study investigates how Islamic education can be integrated with local cultural values amidst modernization and technological change. Its goal is to find effective methods and strategies for implementing culture-based education rooted in local traditions that align with the challenges of the digital age. Using a qualitative approach and a case study design, this research examines practices in Islamic educational institutions, including the use of digital technology—such as online learning and digital platforms—to improve accessibility and understanding. Data were collected through in-depth interviews, participatory observations, and document analysis, then analyzed using thematic analysis. The results show that combining Islamic education with local cultural values is crucial for staying relevant in modern education. Digital technology offers flexible, accessible learning opportunities but also poses challenges in maintaining the authenticity and relevance of Islamic values. Discursive religious practices, involving critical discussion and group analysis, prove effective in fostering a contextual understanding of Islamic values among students despite these challenges. This research adds to the academic conversation by emphasizing the need to integrate technology with local cultural values in Islamic education to stay vital in a globalized world. The limited scope of this study suggests the need for further research, especially comparative studies across different educational settings and the development of technology-based Islamic education models that aim to enhance learning and preserve culture.